2021
DOI: 10.17162/au.v11i5.932
|View full text |Cite
|
Sign up to set email alerts
|

La efectividad de la tecnología de realidad aumentada en la educación STEAM

Abstract: El objetivo de este estudio es identificar el impacto del uso de tecnologías de realidad aumentada en la formación de especialistas en el campo de la educación STEAM, mediante el análisis de indicadores cognitivos como “habilidades” y “voluntad” entre estudiantes que utilizan tecnologías de realidad aumentada, y la comparación entre estos indicadores con un grupo hipotético. El estudio involucró métodos de encuesta, análisis de modelos lógicos y matemáticos del proceso educativo, análisis de factores que influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Other authors such as Delgado-Rodríguez et al ( 2023) and Tsekhmister et al (2022), through a qualitative study of teachers who used augmented reality as a technological resource, showed that teachers require specific training regarding the creation and appropriate use of educational resources and digital evaluation systems. In this regard, Tsekhmister et al (2022), added that "the widespread introduction of innovative technologies in the educational process at all levels has led to the need to create a model for monitoring the quality of teaching and learning, considering new factors influencing the assimilation of new educational resources" (Tsekhmister et al (2022: page 253).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors such as Delgado-Rodríguez et al ( 2023) and Tsekhmister et al (2022), through a qualitative study of teachers who used augmented reality as a technological resource, showed that teachers require specific training regarding the creation and appropriate use of educational resources and digital evaluation systems. In this regard, Tsekhmister et al (2022), added that "the widespread introduction of innovative technologies in the educational process at all levels has led to the need to create a model for monitoring the quality of teaching and learning, considering new factors influencing the assimilation of new educational resources" (Tsekhmister et al (2022: page 253).…”
Section: Resultsmentioning
confidence: 99%
“…Of course, all activities cannot be applied if the teachers who teach STEAM subjects are not adequately prepared for this methodology. According to Tsekhmister et al (2022) the formation of a group of experts in the disciplines involved in STEAM education is the most important procedure, as it largely determines the quality and success of any STEAM activity. Therefore, in the fourth study group, it was considered convenient to evaluate the training of teachers of STEAM disciplines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This publication provides a snapshot of the educational practices shedding light on the historical evolution of teaching methodologies and content in this specialized domain. The study by Tsekhmister, Kotyk, Matviienko, Rudenko and Ilchuk (2021) evaluates the effectiveness of augmented reality technology in Science, Technology, Engineering, Arts, and Mathematics (STEAM) education. This research adds to the growing body of literature exploring the integration of technology, particularly augmented reality, in educational settings and its impact on learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Undoubtedly, one of the fields benefited by the advances in AR technology is education, where several institutions at the primary, middle and higher levels have already implemented the use of this technology as a new pedagogical tool that contributes to learning, research and innovation (Tsekhmister et al, 2022), highlighting the following points:…”
Section: Ar and Its Application In Educationmentioning
confidence: 99%